2019
DOI: 10.1111/acps.13111
|View full text |Cite
|
Sign up to set email alerts
|

How and when to use clozapine

Abstract: Objective Clozapine is the only approved strategy for treatment‐resistant schizophrenia, although it is highly underutilized. We aim to generate practical and actionable evidence‐based recommendations for the use of this drug considering prescription barriers. Method Narrative review. Results A consistent body of evidence supports the efficacy of clozapine reducing morbidity and mortality in schizophrenia. The main obstacles to its use are the lack of experience by prescribers and perceived treatment burden. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 73 publications
2
41
0
Order By: Relevance
“…According to several studies, 30% of patients diagnosed with schizophrenia are resistant to treatment, in which case clozapine should be introduced [47,48]. Our study con rms the underuse of clozapine in treatment-resistant schizophrenia (TRS) [49], being more common antipsychotic augmentation and higher doses of antipsychotic [50]. Overall, the prevalence of clozapine use was signi cantly higher in young patients (15-40 years) and in prevalent users.…”
Section: Discussionsupporting
confidence: 65%
“…According to several studies, 30% of patients diagnosed with schizophrenia are resistant to treatment, in which case clozapine should be introduced [47,48]. Our study con rms the underuse of clozapine in treatment-resistant schizophrenia (TRS) [49], being more common antipsychotic augmentation and higher doses of antipsychotic [50]. Overall, the prevalence of clozapine use was signi cantly higher in young patients (15-40 years) and in prevalent users.…”
Section: Discussionsupporting
confidence: 65%
“…The antipsychotic medication, clozapine, has the most convincing evidence for benefit in treatment-resistant schizophrenia and there are indications that it can reduce aggression, suicidality and mortality in schizophrenia. 1 3 Weighing up the risks and benefits of clozapine treatment in any individual involves the assessment of adverse effects. These include several uncommon but serious problems, such as neutropenia/agranulocytosis, myocarditis/cardiomyopathy, 4 , 5 pneumonia 6 and seizures.…”
Section: Introductionmentioning
confidence: 99%
“…This proportion reflects an underuse of this drug, as research has shown that clozapine is indicated in up to 30% of patients diagnosed with treatment-resistant schizophrenia 50 52 . Instead, these patients are more frequently treated with additional antipsychotics and higher doses 53 . Overall, the prevalence of clozapine use was significantly higher in young patients (15–40 years) and in prevalent users.…”
Section: Discussionmentioning
confidence: 99%